The Influence Of Work Discipline And Work Ethic On The Work Productivity Of Restaurant Construction Workers Kampung Swasana Tasikmalaya - Fery Firmansyah; Cece Rakhmat; Arga Sutrisna (Journal of Indonesian Management, 2022)
This study aims to determine simultaneously and partially the work productivity influenced by Work Discipline and Work Ethic in the Construction of The Swasana Village Restaurant. The method used in this study is a quantitative approach. The sample used was 30 respondents. The data obtained are primary data through questionnaires. The analysis used was multiple linear regression analysis via SPSS Version 24. The results of this study show that work discipline and work ethic simultaneously have a significant effect on Work Productivity. Work discipline partially has a significant effect on work productivity, work ethic partially has a significant effect on work productivity of workers in the construction of Kampung Swasana Restaurant.